Morphology Modification of the Iron Fumarate MIL‐88A Metal–Organic Framework Using Formic Acid and Acetic Acid as Modulators. Issue 18 (11th May 2018) - Bagherzadeh, Elham; Zebarjad, Seyed Mojtaba; Hosseini, Hamid Reza Madaah
Abstract : Metal–organic frameworks (MOFs) are best known for their great structural diversity. The uniformity in the properties of MOFs is mainly governed by the size and morphology of the particles. In the present research, iron‐MIL‐88A was prepared by a modulator‐assisted solvothermal method, and the role of modulating agents in the formation process of MOF particles was investigated. Acetic acid and formic acid were chosen as monoligand modulating agents. The changes in morphology and size distribution of the products were scrutinized by using SEM micrographs. Both modulators clearly interfered with the crystallization process through their attachment to the reactive sites. At low modulator content, the primary diamondlike characteristic morphology of the particles was preserved. While acetic acid mildly altered the morphology of the MOF and narrowed its particle‐size distribution, formic acid drastically changed the morphology of the MOF particles to those resembling dendrites. The structural properties of the products were examined using XRD, FTIR, and TGA studies. Correct amounts of acetic acid improved the crystallinity of the product, while high contents of acetic acid greatly interfered with the formation process and had a paramount effect on the particle morphology evidenced by the decrease in the intensity of diffraction peaks. Abstract : Coordination modulation is an effective way to control the properties of metal–organic frameworks (MOFs). Modulators compete with the bridging ligand of the MOF in attaching to the metallic nodes. In the modulated solvothermal synthesis of Fe‐MIL‐88A, a suitable modulator can control the particle growth and size distribution, the morphology of MOF particles, and improve the crystallinity of the product.